Controlling factors of high-quality reservoirs in low permeability sandstone: a case study of the upper member of the lower Ganchaigou formation, Qaidam basin - Li, Wenhuan; Hu, Dandan; Gong, Changli; Fan, Tailiang; Chen, Yihang; Li, Ya’nan; Shi, Qi; Leng, Qifeng (Frontiers in Earth Science, 2024)
The upper member of the Lower Ganchaigou Formation (UMoLGF) is a highpotential hydrocarbon exploration area in the North margin of Qaidam Basin. It represents a typical low-permeability sandstone reservoir. The current understanding of reservoir characteristics of UMoLGF is poor, and the main controlling factors of high-quality reservoir development remaining unclear. This study, for the first, integrated various factors to investigate the formation mechanism of highquality reservoirs in the UMoLGF's low-permeability sandstone reservoirs. Results show three provenance systems developed in the study area: northwest, northeast, and east. The northwestern and northeastern areas share similar reservoir characteristics.The rock type is predominantly feldspar, with relatively poor particle sorting and rounding. Pore types are dominated by secondary dissolution pores. However, the northwestern area has more developed fractures and poorer pore structures than the northeastern. Meanwhile, in the eastern area, the rock fragment content was high, the rock type was mainly litharentie and lithic arkose, particles were well-sorted and wellrounded. Residual intergranular pores, with good structures, dominated the pore type.The UMoLGF has entered eo-diagenesis B stage with minor progression into meso-diagenesis A stage. Based on quantitive calculations, this study established porosity evolution models for the different study areas. The initial porosities in the northwestern, northeastern, and eastern areas were 30.8%, 30.4%, and 34.8%, respectively. Compaction and cementation are the major factors contributing to porosity reduction in the three areas, with the most significant impact in the northwestern area.Dissolution significantly improved the reservoir properties in the northwestern area, with little effect on the northeastern and eastern areas. The formation of high-quality reservoir in UMoLGF was affected by provenance, diagenesis, and fractures, with the primary controlling factors varying by area. In the northwestern area, the formation of high-quality reservoirs benefited from strong dissolution and well-developed fractures. In the northeastern area, the high-quality reservoir was relied upon favorable provenance and dissolution. In the eastern area, provenance provided an excellent material basis for developing high-quality reservoirs, with dissolution and chlorite cementation further improving reservoir properties. This study provides a theoretical foundation for further exploration and development of UMoLGF and offers insights for exploring and developing similar low-permeability sandstone reservoirs.